2019
DOI: 10.20897/femenc/5919
|View full text |Cite
|
Sign up to set email alerts
|

Mothering in the Context of Poverty: Disciplining Peruvian Mothers through Children’s Rights

Abstract: This article explores discourses surrounding poverty and mothering in the context of Peru. It specifically suggests that claims in the name of children's rights provide a more morally acceptable way to discipline economically disadvantaged mothers. Mothers are framed as 'bad parents' when their children fail to experience so-called 'global childhoods', spent in school and the home, and not in paid work. However, in Andean culture, children begin working alongside their parents at a young age as they learn to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…The findings also revealed that male students perceive more family loneliness than do their female peers. These findings are also consistent with some characteristics and parenting behavior styles that are still dominant in Peruvian society, which are associated with family kinship, household structures, and social stereotypes related to gender roles (Scott, 1990;Aufseeser, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…The findings also revealed that male students perceive more family loneliness than do their female peers. These findings are also consistent with some characteristics and parenting behavior styles that are still dominant in Peruvian society, which are associated with family kinship, household structures, and social stereotypes related to gender roles (Scott, 1990;Aufseeser, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Peruvian mothers, living in a context of poverty, engage their children in vending food and souvenirs on the city streets, bring them to the fields where they work, or rely on children to watch the street food stand while the mother is away (Aufseeser, 2019). Mothers are aware of street risks but, as they very often raise their children alone, they struggle to create care networks to protect their children while on the street.…”
Section: Reclaiming Motherhoodmentioning
confidence: 99%
“…To this end, they apply complex strategies where the child’s well-being is integrated into the family’s well-being; yet they are criticized, more often than not, as ‘bad mothers’ for non-compliance with global perceptions of ‘good childrearing’. They, too, often portray motherhood as altruistic – for the benefit of the children whom they consider as a gift, given to save them from loneliness and disarray (Aufseeser, 2019: 8).…”
Section: Reclaiming Motherhoodmentioning
confidence: 99%